Miss Button and the School Board B.2 - Boonstra, Jean; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2002)
In 1843 Sarah's teacher, Miss Button, is fired from her country school because of her views on the imminent second coming of Christ, but at the school board meeting she finds an unlikely champion.
Keywords: Story Collection